2021
DOI: 10.1111/nan.12737
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in post‐mortem imaging‐histopathology studies of sporadic human cerebral small vessel disease: A systematic review

Abstract: Aims Sporadic human cerebral small vessel disease (SVD) commonly causes stroke and dementia but its pathogenesis is poorly understood. There are recognised neuroimaging and histopathological features. However, relatively few studies have examined the relationship between the radiological and pathological correlates of SVD; better correlation would promote greater insight into the underlying biological changes. Methods We performed a systematic review to collate and appraise the information derived from studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 95 publications
(540 reference statements)
3
28
0
Order By: Relevance
“…These changes are more frequent in KO animals ( Fig. 2G ), indicating EC dysfunction at an ultrastructural level, consistent with structural abnormalities seen in small perforating brain blood vessels in human SVD(27). Not all blood vessels are affected, with heterogeneity between vessels even within animals ( Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…These changes are more frequent in KO animals ( Fig. 2G ), indicating EC dysfunction at an ultrastructural level, consistent with structural abnormalities seen in small perforating brain blood vessels in human SVD(27). Not all blood vessels are affected, with heterogeneity between vessels even within animals ( Fig.…”
Section: Resultssupporting
confidence: 78%
“…Not all blood vessels are affected, with heterogeneity between vessels even within animals ( Fig. 2H ), highlighting the well-recognised focal nature of SVD as found in humans(27).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Using these conventional diffusion measures, previous studies have suggested that potential pathological processes underlying WMH may be related to demyelination and reduced axonal density (Wardlaw, Valdés Hernández and Muñoz-Maniega, 2015; Muñoz Maniega et al ., 2017). Furthermore, recent studies indicate that an increase of extracellular free-water (FW) (Pasternak et al ., 2009), measured using dMRI, may be an early pathological process in CSVD (Duering et al ., 2018; Wardlaw, Smith and Dichgans, 2019; Humphreys, Smith and Wardlaw, 2021) and is a sensitive marker of cognitive performance in aging (Maillard et al ., 2019). While associations between white matter microstructure and cognitive performance are found throughout the white matter in CSVD (Table 1), thus far the superficial white matter microstructure has not been specifically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…First, the effect of WMH is widespread. A recent review summarizes postmortem histological and MR imaging studies of CSVD, which have reported extensive white matter lesions with SWM involvement (Humphreys, Smith and Wardlaw, 2021). In addition, progression of WMH is known to spread from deeper to more superficial white matter regions during the course of CSVD (Lambert et al ., 2016; van Leijsen et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%